Peningkatan Sumber Daya Manusia Kelompok Sadar Wisata Dalam Pengelolaan Pantai Indah Kemangi Kabupaten Kendal - Muchammad Satrio Wibowo; Herman Novry Kristiansen Paninggiran; Urania Heptanti (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
Increased understanding of human resources is an important capital in the process of managing a destination. This can make people move more effectively and efficiently. The community service partner is the Sidodadi Jungsemi Village Owned Enterprise (BUMDes). BUMDes cooperates with Pokdarwis (Tourism Awareness Group) and the Village Consultative Body to manage Indah Kemangi Beach, Jungsemi Village, Kendal Regency. Weaknesses felt by partners, namely the lack of understanding of community participation in the management of Indah Kemangi Beach. The purpose of this activity is to increase understanding of community participation in the management of Pantai Indah Kemangi. The theme of the service material is the importance of the community and organizations in the village. This service uses the method of giving direct lectures and questions and answers with participants. Assessment of understanding was carried out using the pre-test and post-test methods. The understanding index value during the pre test ranged from 48.5% - 58.6%, included in the lack of understanding category. The index value during the post test ranged from 65.7% - 70%, included in the understanding category. There is an increase in understanding of the material presented. Understanding human resources is the main capital in managing a destination. Existing knowledge and abilities are used to understand problems and then find solutions from within themselves.